1996
DOI: 10.1006/jsre.1996.0293
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Neuromuscular Function after Preservation and Transplantation

Abstract: While it is well known that prolonged preservation of the intestinal graft causes severe mucosal damage after transplantation, little is known about the effect on neuromuscular function. The entire small intestine of adult hound dogs was flushed and preserved with cold lactated Ringer's solution and autotransplanted either immediately (n = 6) or after 24 hr (n = 6). Animals undergoing sham operation (n = 4) were used as a control. Fasting motility and the response of the intestinal smooth muscle and enteric ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 23 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…Moreover, if a whole intestine or jejunal graft is used, it can be reimplanted in continuity with the liver, but it may be easier technically to transplant the two organs separately. Separating the two organs at the back table results in increased cold ischemia time, which adversely affects intestinal motility [7]. This factor could be responsible for the initial absence of peristaltic waves of the graft in our patient.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, if a whole intestine or jejunal graft is used, it can be reimplanted in continuity with the liver, but it may be easier technically to transplant the two organs separately. Separating the two organs at the back table results in increased cold ischemia time, which adversely affects intestinal motility [7]. This factor could be responsible for the initial absence of peristaltic waves of the graft in our patient.…”
Section: Discussionmentioning
confidence: 81%
“…They concluded that the preservation time and the type of solution determined the viability of the graft. Hamada et al [22] reported that, in a transplanted dog model using lactated Ringer's solution, the reappearance of MMC in the graft occurred 2 days postoperatively in immediately transplanted group, whereas in the 24h preservation group, it took 3 weeks after transplantation. In our study, using lactated Ringer's solution and bimmediate transplantation,Q MMC reappeared by at least 5 POD in the graft, so the data obtained in this study were thought not to be affected by preservation injury.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, abnormal motility has been described after SBTx [16][17][18] . The imp airment of the intrinsic neural tissues has resulted in serious alterations of coordinated motility patt erns.…”
Section: Discussionmentioning
confidence: 99%